2018
DOI: 10.1007/s10567-017-0252-3
|View full text |Cite
|
Sign up to set email alerts
|

Review of a Parent’s Influence on Pediatric Procedural Distress and Recovery

Abstract: Understanding how parents influence their child's medical procedures can inform future work to reduce pediatric procedural distress and improve recovery outcomes. Following a pediatric injury or illness diagnosis, the associated medical procedures can be potentially traumatic events that are often painful and distressing and can lead to the child experiencing long-term physical and psychological problems. Children under 6 years old are particularly at risk of illness or injury, yet their pain-related distress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 190 publications
1
61
0
2
Order By: Relevance
“…A limitation of the present study was that only the patient's psychological factors were evaluated in isolation to the parental ones. Studies have shown that parental psychological factors also play an important role in their children's response to pain [36,37]. Rabbitts et al (2014; observed that parental pain catastrophizing had a significant impact on pain trajectory membership, such that higher parental pain catastrophizing led to greater pain intensity in the acute postoperative period and late recovery after surgery [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the present study was that only the patient's psychological factors were evaluated in isolation to the parental ones. Studies have shown that parental psychological factors also play an important role in their children's response to pain [36,37]. Rabbitts et al (2014; observed that parental pain catastrophizing had a significant impact on pain trajectory membership, such that higher parental pain catastrophizing led to greater pain intensity in the acute postoperative period and late recovery after surgery [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Given the association between pain and post-traumatic stress in children, 36 these sex differences in opioid administration may reflect underlying processes that affect the psychological response to traumatic injury. There is a need for increased awareness of communication and behaviors expressed by parents and providers toward each other and the child during the evaluation and management of pain in the pediatric trauma population, as these communications may be influenced by level of distress 37 and preconception about pain. [38][39][40] Providers should also look for opportunities to have discussions with patients and their families about communicating levels of pain and appropriate expectations of pain management during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Parental anxiety and PTSS have been found to influence child procedural coping and distress behaviours through reduced parental coping-promoting and increased distress-promoting behaviours (Brown, De Young, Kimble, & Kenardy, 2019). Largely, parental behaviour during paediatric medical procedures has been related to child procedural coping and distress, and child procedural pain/fear (for a review, see Brown et al, 2018b). Given the role pain plays in wound healing, there is a potential cascade of parental acute psychological distress influencing child re-epithelialization through parenting behaviour influencing child pain severity.…”
Section: Statement Of Contributionmentioning
confidence: 99%
“…It is common for parents to experience psychological distress, including anxiety, guilt, and PTSS following a paediatric burn (Bakker, Van Loey, Van der Heijden, & Van Son, 2012;Stoddard et al, 2006). Largely, parental behaviour during paediatric medical procedures has been related to child procedural coping and distress, and child procedural pain/fear (for a review, see Brown et al, 2018b). Largely, parental behaviour during paediatric medical procedures has been related to child procedural coping and distress, and child procedural pain/fear (for a review, see Brown et al, 2018b).…”
mentioning
confidence: 99%